The Problem of Sanctions in International Law: Aspect of Terminology - Ekaterina M. Ivanova (Московский журнал международного права, 2016)
The article analyzes the problem of sanctions in international law. Special attention is given to the absence of a uniform approach to the definition of the term "sanctions". Different practical interpretations of the term "sanctions" are given. The term "sanction" is considered in the context of domestic and international law. The necessity of development of the legal framework and practice of law enforcement is determined and proved.